Zgodovina raziskovanja luminiscentnih snovi - Južnič, Stanislav (Vakuumist, 1997)
The development of the research of the luminiscent materials is described frominventions to their use in Braun's cathode ray tube. Attention is put on the researches and writing about luminiscence in Austria, specially in its Slovene part. The second part of the discussion begins with Stokes' law in themiddle of the last century. We describe in some detail only modern researchin cathodo-luminiscence and electroluminiscence.
Keywords: fizika; physics; luminiscenca; zgodovinski prikazi